Disrupted circadian rhythms in a mouse model of schizophrenia. - Oliver, P; Sobczyk, M; Maywood, E; Edwards, B; Lee, S; Livieratos, A; Oster, H; Butler, R; Godinho, S; Wulff, K; Peirson, SN; Fisher, S; et al. (2012)
Sleep and circadian rhythm disruption has been widely observed in neuropsychiatric disorders including schizophrenia [1] and often precedes related symptoms [2]. However, mechanistic basis for this association remains unknown. Therefore, we investigated the circadian phenotype of blind-drunk (Bdr), a mouse model of synaptosomal-associated protein (Snap)-25 exocytotic disruption that displays schizophrenic endophenotypes modulated by prenatal factors and reversible by antipsychotic treatment [3, 4]. Notably, SNAP-25 has been implicated in schizophrenia from genetic [5-8], pathological [9-13], and functional studies [14-16]. We show here that the rest and activity rhythms of Bdr mice are phase advanced and fragmented under a light/dark cycle, reminiscent of the disturbed sleep patterns observed in schizophrenia. Retinal inputs appear normal in mutants, and clock gene rhythms within the suprachiasmatic nucleus (SCN) are normally phased both in vitro and in vivo. However, the 24 hr rhythms of arginine vasopressin within the SCN and plasma corticosterone are both markedly phase advanced in Bdr mice. We suggest that the Bdr circadian phenotype arises from a disruption of synaptic connectivity within the SCN that alters critical output signals. Collectively, our data provide a link between disruption of circadian activity cycles and synaptic dysfunction in a model of neuropsychiatric disease.